Associations between primary care continuity, illness perception, and hypertension control among hypertensive patients in Kon Tum province, Vietnam - Nguyễn, Minh Tâm; Hồ, Đắc Trường An; Lê, Hồ Thị Quỳnh Anh; Chế, Thị Len Len; Phan, Thuý Hồng; Huynh, Van Minh (Tạp chí Y học lâm sàng Bệnh viện Trung Ương Huế, 2025)
Background: In low-resource settings, hypertension control in primary care is challenging. Continuity of care (COC) and illness perception (B-IPQ) play crucial roles in hypertension management, yet their association with blood pressure (BP) control remains unclear. This study aims to examine the interplay of COC and illness perception on BP control among hypertensive patients. Methods: A cross-sectional study was conducted among 397 hypertensive patients attending commune health centers in Kon Tum province, Vietnam. COC was assessed using the Continuity of Care Index (COCI), illness perception was measured using the Brief Illness Perception Questionnaire (B-IPQ), and BP control was defined as <140/90 mmHg. Multivariate logistic regression was performed to evaluate the associations between COC, B-IPQ, and BP control. Results: BP control was achieved by 54.7% of participants. While continuity of care index (COCI) was high (94.2%), it was not associated with BP control (p > 0.05). In contrast, higher illness perception (B-IPQ) scores, observed in 44.6% of participants, were consistently linked to better BP control (OR = 1.02 - 1.03, p < 0.05). Urban residence, female gender, BMI, and medication adherence were strong predictors (p < 0.05). Conclusions: Illness perception is a key determinant of BP control, while visit-based COC alone does not appear to be a determining factor. Continuity in provider-patient relationships and structured patient education may be necessary to translate high COC into better BP outcomes. Enhancing illness perception through targeted interventions and ensuring quality interactions within primary care settings could improve hypertension management, particularly in rural healthcare contexts.